Tomorrow perhaps the future : writers, outsiders, and the Spanish Civil War - Watling, Sarah (Alfred A. Knopf, 2023)
"An account of extraordinary artists and activists whose determination to live - and to create - with courage and conviction took them as far as the Spanish Civil War"--